Artificial Intelligence and the Semantics of Change: Narratives, Languages and Values (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The paper proposes a reflection on the topic of Artificial Intelligence from the perspective of analytical legal philosophy, which uses linguistic analysis to clarify meanings of concepts deployed in three different, albeit interrelated, languages: institutional and political languages, legal language, and ordinary language. It is indeed through these three linguistic vectors that deep transformations of society are narrated. These narratives and their languages shape how societal changes are collectively and individually perceived and experienced. Control over languages and concepts is therefore important to guide these transformations in line with the fundamental rights framework as will be argued in this paper.
Keywords: semantics; analytical philosophy; AI; narratives; anthropomorphism